Acetaldehyde and formaldehyde concentrations from sites impacted by heavy-duty diesel vehicles and their correlation with the fuel composition: Diesel and diesel/biodiesel blends - Rodrigues, Marina C. (2012)
texto completo: acesso restrito. p. 258–263.